Intraoperative Label‐Free Photoacoustic Histopathology of Clinical Specimens. Issue 10 (16th August 2021) - Baik, Jin Woo; Kim, Hyojin; Son, Myeongjoo; Choi, Junwon; Kim, Kwang Gi; Baek, Jeong Heum; Park, Yeon Ho; An, Jungsuk; Choi, Hae Young; Ryu, Seon Young; Kim, Jin Young; Byun, Kyunghee; et al.
Abstract: During cancer resection surgeries, intraoperative histopathologic examination of the surgical specimen is crucial for tumor margin identification. A conventional frozen‐section analysis requires complex tissue processing, which prolongs surgery and potentially introduces interpretation errors. Here, as a novel approach to label‐free intraoperative histopathology, a high‐speed reflection‐mode ultraviolet photoacoustic microscopy (UV‐PAM) system employing a waterproof 1‐axis microelectromechanical systems scanner is demonstrated. Label‐free nuclear imaging is photoacoustically verified using tissue sections excised from mice and humans. Moreover, by imaging clinical specimens from cancer patients and numerically quantifying the histopathologic results, it is successfully demonstrated that the proposed UV‐PAM system has great potential as an alternative intraoperative histopathology method with minimal tissue preparation processes. Abstract : Here, high‐speed, label‐free, and non‐destructive intraoperative histopathology is introduced with the first PA clinical trials according to the diagnostic grades of thick cancer specimens, demonstrating the multi‐feature analysis using a supervised learning algorithm. This approach has the potential for pathologists to differentiate suspicious cancer region accurately, which can be linked to subsequent postoperative examination.